Managing the northern supply haul: legal aspect - M. E. Kuznetsov; M. I. Nikishova (Russian Journal of Economics and Law, 2022)
Objective: to evaluate the regulatory legal mechanisms of the management of the Northern supply haul to the Far North regions and to formulate proposals for their improvement.Methods: a spatial approach that allowed us to consider the management of the Northern supply haul through the conceptualization of the spatial dimension of the remote areas supply processes – the predestination of a certain geographical coordinate system in which the object under study is placed, and the presence of regionalization determined by the spatial and temporal structuring of the territory of our country; interviewing and focus groups with executive authorities, representatives of research institutes, expert and business communities in order to form an array of initial data on the legal aspects of the Northern supply haul.Results: the article states that regional regulatory legal acts are predominantly non-systemic in nature (except in the Republic of Sakha (Yakutia)), regulating certain areas of state support, in particular the procedure for providing financial support. The low demand for other types of support is due to the need to form incentives for the participation of economic entities in the Northern supply haul under low business margins. The difficulty lies in the need to integrate centralized and decentralized supply systems in the absence of an appropriate legal framework.Scientific novelty: for the first time, an assessment of the effectiveness of state support measures for the Northern supply haul was carried out to determine the directions for improving its legal mechanisms. The definition of the Northern supply haul and categorization of these areas by periods of transport communication are proposed. The improvement of legal regulation based on the development of a single law with the definition of the rules for stakeholders is proposed.Practical significance: the presented assessment of the legal mechanisms of the Northern supply haul management and the formation of proposals for their improvement can be useful for correcting the existing and developing a new approach to the development of a specialized regulatory legal framework at both the federal and regional levels. The recommendations can be used by executive authorities in the development of state policy and regulatory regulation of life support issues in the northern territories.